محافظ الحسابات ودوره في دعم وتحسين جودة المراجعة الخارجية - شاهد, إلياس; رور, عبد النعيم; عياشي, الأخضر (جامعة الوادي - University of Eloued, 2017)
عتبر دور محافظ الحسابات في الفحص الدقيق للحسابات والتأكد والتحقق من أن جميع المعلومات والبيانات المالية الواردة في القوائم والتقارير المالية على درجة عالية من المصداقية والسلامة من الأخطاء والتناقضات الواردة في التسجيلات المحاسبية الأولية. ويتمثل محافظ الحسابات في شخص طبيعي ، أو شخص معنوي والمتمثل في شركات المراجعة. بعد توفر الشروط اللازمة لمزاولة المهنة الخاصة بمراجعة الحسابات للمؤسسة. وفي الأخير يصل إلى إبداء رأي محايد يعبر عن مدى مصداقية البيانات والمعلومات المحاسبية الخاصة بالمؤسسة محل المراجعة. ويتم ذلك عبر خطوات متعارف عليها في القانون والعرف المحاسبي الدولي. ويجب أن يصل إلى أن التسجيلات المختلفة التي تمت في سجلات المؤسسة أنها خالية من الأخطاء سواء كانت بالقصد أو بدون قصد. ومحاولة إصلاحها لتستفيد المؤسسة من عملية المراجعة الخارجة كتغذية عكسية لها. أما جودة المراجعة تعني صدق المعلومات المحاسبية والمالية التي تتضمنها التقارير المالية وما تحققه من منفعة للمستخدمين ولتحقيق ذلك يجب أن تخلو من التحريف والتضليل وأن تعد في ضوء مجموعة من المعايير القانونية والرقابية والمهنية والفنية, بما يحقق الهدف من استخدامها. The role of the governor of accounts is to scrutinize, verify and verify that all information and financial statements contained in the financial statements and reports are highly credible and safe from errors and inconsistencies contained in the initial accounting records. The governor of accounts is a natural person, or a legal person, represented by audit firms. After providing the necessary conditions for practicing the audit profession of the institution. Finally, a neutral opinion is expressed which expresses the credibility of the accounting data and information of the institution under review. This is done through customary steps in international accounting law and practice. It should be noted that the various registrations made in the Foundation's records are free of errors, either intentionally or unintentionally. And try to reform the institution to benefit from the process of auditing emerging as a back-feed. The quality of the audit means the accuracy of the accounting and financial information contained in the financial reports and the benefit they have achieved for the users and to achieve this must be free from distortion and misleading and prepared in the light of a set of legal standards, control, professional and technical, to achieve the purpose of its use
Governor of Accounts and his role in supporting and improving the quality of external audit
مقال
Keywords: :المراجعة الخارجية ،محافظ الحسابات، التقارير المالية ، المعلومات المحاسبية ،جودة المراجعة; external audit, portfolio manager, financial reporting, accounting information, audit quality